The extent of the late cenozoic glaciation in the Central Highlands of Tasmania, Australia. - Kiernan, K (1990)
It is argued that during the most extensive late Cenozoic glaciation of the Tasmanian Central Highlands an ice cap of ~ 6000 km2 developed, probably in the early Pleistocene or late Pilocene. At least three subsequent glaciations have occurred. During the late Last Glacial Stage smaller ice caps were present on the Central Plateau, on a number of smaller plateaus, and on the West Coast Range and other ranges. The more westerly glaciers displayed the highest rates of mass throughout. The ice masses were of temperate maritime character. It is not necessary to invoke any significant shift in the direction of snow-bearing winds to explain the pattern of glaciation when the ice was most extensive.